Impact of common shade tree species on microclimate and cocoa growth in agroforestry systems in Ghana - Kohl, Theresa; Niether, Wiebke; Abdulai, Issaka; Justus Liebig University Giessen (My University, 2024)
Climate change is a growing threat to agriculture globally, with most substantial impacts expected in tropical smallholder systems such as cocoa farms in West Africa. Cocoa agroforestry is widely believed to enhance resilience to climatic extremes due to protection and a favourable microclimate under the shade trees. Morphological traits of many locally used shade tree species and their specific contribution to microclimate for climate-resilient cocoa production remain unclear. Therefore, aboveground morphology and sub canopy microclimate of eight common shade tree species were investigated in cocoa agroforestry systems in the Ahafo region, Ghana. Additionally, the growth of cocoa trees in three different distance zones to the shade tree stem was measured. The eight different shade tree species exhibited considerable variation in their impact on microclimate and cocoa growth. M. indica and M. excelsa allowed lowest light transmission, with the highest microclimatic buffering effect, i.e., reducing vapour pressure deficit and daily fluctuations of temperature and relative humidity. Cocoa trees around M. lucida and F. capensis were the highest in growth, characterized by height and stem diameter. However, a universally superior shade tree species could not be identified implying the need for shade tree diversity allowing various microclimatic conditions within an agroforestry system to spread risk of climate extremes. Cocoa tree growth was more affected by distance to the shade tree than by shade tree species, resulting in enhanced growth with distance to the stem. These findings provide a better understanding of species-related differences on cocoa growing conditions and climate change adaptation strategies.
Keywords: ddc:630